(untitled) (Universal Technical Journal of Lumbini International Academy of Science and Technology, 2025)
Bagmati River originates from Northern hills of Kathmandu valley and flows through the middle of the valley. Kathmandu valley is vulnerable to flood hazard due to rapid encroachment of settlement in flood plains of the Bagmati River. This objective of this study is analyzing the flood hazard and risk of settlement at the bank of Bagmati River from Shankhamul to Balkhu of Kathmandu valley and the expected number of people affected. The flooded areas along the catchment area have been mapped based on the flow rates for different return periods using the HEC-RAS model and GIS for spatial data processing and Analysing the result from HEC-RAS 6.3.1. The areas along the Bagmati River from Shankhamul to Balkhu in the study area were simulated to be inundated for 50 and 100 years return periods. An inundation map displays the spatial extent of probable flooding for different scenarios and can be present either in quantitative or qualitative ways. The flood inundation maps for 50 and 100 years return periods were prepared using HEC RAS and Risk on the basis of depth map generated from Arc Map GIS. Population under risk is analyze on the basis of population density and Inundated area. The major findings in the study is 31391 & 32141 Population and 1.835575 & 1.879375 km2 area are in the inundated in 50 and 100 years return Period respectively. Therefore, proper flood management can be adopted to reduce the adverse effects of flooding of Settlement living at the bank of Bagmati River.